Kitab Tafsir Karya Ulama Aceh; Al-Quran Al-Karim Wa Bihamisihi Turjuman Al-Mustafid - Elkarimah, Mia Fitriah; Sa'dullah, Sa'dullah (ZAD Al-Mufassirin, 2023)
This article discusses the Al-Qurān Al-Karīm Wa Bihāmisihi Turjumān Al-Mustafīd by Sheikh Abdurrauf As-singkili in a manuscript copy in the national library. The results of the research show that the Tarjuman Al Mustafid manuscripts that were obtained were 4 manuscripts with collection codes ML 322, ML 291, ML 373 and A 233. Meanwhile, the A 233 code examined was colored red for the text of the verses of the Koran and black ink. for interpretation. Meanwhile, the cover is thick cardboard covered with green marble paper. This manuscript is 3 cm thick. Meanwhile, to analyze this manuscript, the author refers to the Turjuman al-Mustafid manuscript, a digital edition published by Musthafa al-Babi al-Halabi in 1951 which is available in the LPMQ library of the Jakarta Ministry of Religion. This text contains several codes, including فائدة which explains the differences between qira'at, قصة which explains asbabunnuzul. This Tafsir Tarjuman text tends to be of the al-ijtima'i style seen in the interpretation of Al-Baqarah verse 184. Meanwhile, a small note regarding the writing, there are several errors in the writing of the qiroat imam, such as abu Umr (should be Abu 'Amr) "أبو عمر which should be أبو عمرو and ibn Zakwan ابن زكوان which should be ابن ذكوان Ibn Dzakwan.